Multimodal movement planning: logistics network and analysis of transportation alternatives. study case - Figueroa, Miguel; Mora Lerma, Otto; Fuentes, Ricardo; Ojeda, Alfredo (International Journal of Engineering and Technology, 2019)
One of the most relevant problems in transport engineering is the planning of multimodal movements where it is necessary to define the logistics network. To analyze the logistics of a foreign trade operator in Colombia, a mathematical model has been designed for the choice of ports, considering multimodal transport and the state of the art. Initially, a multimodal network was built considering modes of maritime, river, rail and road transport, taking advantage of the main river of Colombia (Magdalena river) and the railway infrastructure. Port operating costs, transshipment, port fees, sea freight, operational and variable costs were included in the analysis. It was found that the most suitable ports in Colombia for export are Cartagena and Buenaventura, with the current infrastructure and demand. It has been found that multimodal arcs are more used than those with a single mode, in addition to exports to Ecuador being made by Buenaventura, while to America and Europe is Cartagena. Additionally, there is sensitivity in the choice of ports concerning the level of prices of road transport since in the Colombian context it is vital to change transfers due to the lack of connectivity between modes such as rail and river.Â Â Â